Міцність внутрішнього корпуса парової турбіни - Пальков, Сергій (КІНПАТРІ ЛТД, 2013)
The solution of the problem of the stress-strain state of the inner case of the steam turbine in an elastic formulation is presented. Also, the results of research in the form of the field of the stress, strain and contact pressure at the reference sites of the flanged connection inner case are presented.
The strength of the inner case of the steam turbine